Development of a tastemaker from bamboo shoot and traditional nutritional spices of North-East India - Begum, Ninja; Sharma, Deboja; Dutta , Pratikshya (Journal of Postharvest Technology, 2021)
Development of a new product is a challenging area in the field of food processing. Consumers today are very enthusiastic to try ready-to-make products that are delicious as well as nutritious. On the other hand, North East India is a hub of indigenous spices known for their unique flavor and health benefits. Keeping these into consideration this study was designed to formulate a spice mix using bamboo shoot and traditional nutritional spices from North East India that adds a good flavor to the dishes. Along with it the physico-chemical and organoleptic attributes of the developed product was analyzed for consumer acceptability. From the results it can be concluded that the developed spice mix has a great potential in today’s market scenario where delicious, ready-to-make, nutrients packed and low-fat products are on huge demand. The study also highlights the need of further exploration of locally available foods in the North-East India.